KADERISASI GURU DAN DOKTER GIGI DI NAGARI UJUNG GADING KECAMATAN LEMBAH MELINTANG PASAMAN BARAT - Haria Fitri; Rahmi Khairani Aulia; Novia Wirna Putri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Dental caries is a major health issue commonly affecting children in Indonesia, including those in Lembah Melintang District, West Pasaman. To support the Indonesia Free of Caries 2030 program, preventive efforts are needed through the training and empowerment of school-level dental health agents, known as